Influence of Zonal Wind Velocity Variation on Equatorial Plasma Bubble Occurrences Over Southeast Asia - Idahwati Sarudin; Nurul Shazana Abdul Hamid; Mardina Abdullah; Suhaila M. Buhari; K. Shiokawa; Yuichi Otsuka; Kornyanat Hozumi; Punyawi Jamjareegulgarn (Journal of Geophysical Research Space Physics, 2021)
Abstract The present study aims to investigate the influence of the zonal wind velocity on equatorial plasma bubble (EPB) occurrences over Southeast Asia. The observation of the EPB occurrence is obtained from the GPS Rate of TEC change index. Meanwhile, the zonal winds were measured using a Fabry‐Perot interferometer located at Kototabang and Chiang Mai stations, and the height of F layer was acquired using an ionosonde at Chumphon station near the magnetic equator. This is the first study to report the influence of zonal wind velocity variation on EPB occurrences with the presence and absence of EPB using GPS data in the Southeast Asian sector. The results illustrated that the average magnitude of zonal wind velocity during the presence of EPB (78 ± 23 m/s) was higher than that of its absence (68 ± 21 m/s). It was observed using long‐term data analyses which led to in‐depth analyses. The analysis of temporal variation of zonal wind variation demonstrated that the zonal winds during EPB were higher in the evening compared to midnight and postmidnight periods from medium to high solar activities. The dependence of zonal wind velocity on EPB over local time was obtained based on the analysis which utilized the data collected during equinox in high solar activity. Besides that, a positive correlation was obtained between the zonal wind velocity and EPB occurrences during pre‐reversal enhancement (PRE) corroborated the effects of zonal wind influence on PRE, and thus EPB occurrences.
Keywords: Ionosphere and magnetosphere dynamics; Oceanographic and Atmospheric Processes; Solar and Space Plasma Dynamics